Genome-Wide Analysis of Myeloblastosis-Related Genes in Brassica napus L. and Positive Modulation of Osmotic Tolerance by BnMRD107 - Li, Jian; Lin, Keyun; Zhang, Shuai; Wu, Jian; Fang, Yujie; Wang, Youping (Frontiers in Plant Science, 2021)
MYB-related transcription factors comprise a large subfamily of the MYB family. They play significant roles in plant development and in stress responses. However, MYB-related proteins have not been comprehensively investigated in rapeseed (Brassica napus L.). In the present study, a genome-wide analysis of MYB-related transcription factors was performed in rapeseed. We identified 251 BnMYB-related members, which were divided phylogenetically into five clades. Evolutionary analysis suggested that whole genome duplication and segmental duplication events have played a significant role in the expansion of BnMYB-related gene family. Selective pressure of BnMYB-related genes was estimated using the Ka/Ks ratio, which indicated that BnMYB-related genes underwent strong purifying selection during evolution. In silico analysis showed that various development-associated, phytohormone-responsive, and stress-related cis-acting regulatory elements were enriched in the promoter regions of BnMYB-related genes. Furthermore, MYB-related genes with tissue or organ-specific, stress-responsive expression patterns were identified in B. napus based on temporospatial and abiotic stress expression profiles. Among the stress-responsive MYB-related genes, BnMRD107 was strongly induced by drought stress, and was therefore selected for functional study. Rapeseed seedlings overexpressing BnMRD107 showed improved resistance to osmotic stress. Our findings not only lay a foundation for further functional characterization of BnMYB-related genes, but also provide valuable clues to determine candidate genes for future genetic improvement of B. napus.